Growth Parameters of DK8031 Maize Variety as Affected by Varying Irrigation and Nitrogen Fertilizer Rates in Embu County, Kenya - Onyari, Charles N.; Kibe, Antony M.; Mwonga, Samuel (David Publishing, 2015)
Determination of crop growth parameters of maize helps assess the performance of the crop for food security. A study was conducted in two seasons covering 2012 and 2013 to establish optimal irrigation and nitrogen fertilizer rates for drought tolerant hybrid maize (Zea mays L.), DK8031 variety, in sandy loam soils using furrow irrigation. Four additive irrigation levels (119.05 mm, 238.10 mm, 357.15 mm and 476.2 mm) were allocated the main plots while five nitrogen fertilizer rates (0 kg/ha, 60, 75 kg/ha, 90 kg/ha and 100 kg/ha) were allocated the sub-plots. Both irrigation and nitrogen fertilizer treatments significantly enhanced crop growth parameters under consideration. Stand count per treatment plot, plant height and number of leaves per ranged from 45-59 plants/plot, 215-238 cm and 14-16 leaves respectively. It was concluded that use of supplementary irrigation and phased nitrogen fertilizer rates for maize growing in areas such as Embu can greatly promote crop growth.
doi:10.17265/2162-5298/2015.08.005
Keywords: Maize; irrigation; nitrogen fertilizer rates; plant height; leaves per plant